2014
DOI: 10.5943/mycosphere/5/2/11
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Semi-Arid Ascomycetes I: new and interesting records of hysteriaceous ascomycetes

Abstract: During an investigation of ascomycetes carried out in one area of Caatinga and three enclaves of the Atlantic Forest in the semi-arid region of Brazil, we found ten interesting species of hysteriaceous ascomycetes. Psiloglonium clavisporum and Rhytidhysteron opuntiae are new records for South America and Anteaglonium abbreviatum, Hysterium angustatum and Hysterobrevium smilacis are new records for Brazil. All species are described, illustrated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
4
0
5
Order By: Relevance
“…Aunado a esto crece sobre frondas caídas de helechos en zonas templadas de Alemania, España e Inglaterra (Dennis, 1981). También ocurre en Brasil, sobre corteza no identificada, creciendo en bosque tropical seco (Almeida et al, 2014). Otras especies con ascosporas con tres septos son G. abietina Sid., G. lapponica (P.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Aunado a esto crece sobre frondas caídas de helechos en zonas templadas de Alemania, España e Inglaterra (Dennis, 1981). También ocurre en Brasil, sobre corteza no identificada, creciendo en bosque tropical seco (Almeida et al, 2014). Otras especies con ascosporas con tres septos son G. abietina Sid., G. lapponica (P.…”
Section: Resultsunclassified
“…Murillo et al (2009) la citan de amplia distribución en Costa Rica, e incluyen ejemplares de Estados Unidos, Puerto Rico y Venezuela. Almeida et al (2014) la mencionan de Argentina, Brasil, China, Costa Rica, Cuba, Dominica, Estados Unidos de América, Filipinas, Francia, Ghana, India, Islas Cook, Jamaica, Japón, Kenia, Malasia, Micronesia, Nueva Guinea, Nueva Zelanda, Puerto Rico, Sierra Leone, Tanzania y Tonga. En México ha sido citado por Méndez-Mayboca et al (2010) de Sonora y por Chacón et al (2014) de Chiapas, Guerrero, Nuevo León, Puebla, Querétaro, Quintana Roo, Sonora, Tabasco, Tamaulipas y Veracruz y en el presente trabajo se registra por primera vez para Oaxaca.…”
Section: Resultsunclassified
“…A survey of ascomycetes in three enclaves of Atlantic Forest in the Caatinga biome of Brazil was performed from 2011 to 2013, resulting in the collection of 460 specimens. The ongoing study of these specimens has already resulted in the descriptions of seven new species and a new genus (Almeida et al 2014b), while new and interesting records were reported in Almeida et al (2014a). In this paper we provide descriptions and illustrations for five additional records to add to the increasing knowledge of this group in Brazil.…”
Section: Introductionmentioning
confidence: 89%
“…Study area and morphological Study: Samples of dead twigs and decaying wood were collected from March 2011 to May 2013 in three enclaves of Atlantic Forest in the Caatinga biome of the semiarid region of Brazil. Description of the study area and methods for collection and morphological examination of specimens have been previously described (Almeida et al 2014b, Almeida et al 2014a. Specimens are deposited in the Herbarium of the State University of Feira de Santana (HUEFS).…”
Section: Methodsmentioning
confidence: 99%